The Effect of Spirituality on the Subjective Recovery of Psychiatric Patients - CAN ÖZ, Yüksel (Journal of religion and health, 2021)
Spiritual well-being is among the factors that affect subjective recovery. This study aimed to explore the relationship between subjective recovery and spiritual well-being among psychiatric patients and to identify the factors that affected their subjective recovery. A descriptive, cross-sectional study was conducted with 96 patients admitted to the psychiatry clinic of a hospital. It was found that the patients had high subjective recovery assessment levels and medium levels of spiritual well-being. There was a positive association between the patients’ subjective recovery assessments and their spiritual well-being, and spiritual well-being was a significant predictor of the subjective recovery level. It is recommended that mental health professionals focus on serving patients through a holistic healthcare approach and enhancing patients’ subjective recovery levels through applications that will strengthen the spiritual dimension.